PELATIHAN PEMBUATAN PRODUK OLAHAN KELAPA DALAM MENUMBUHKAN MINAT WIRAUSAHAPADA KELOMPOK PKK KELURAHAN MALALAYANG DUA, KOTA MANADO - Juliet Truly Pauladel Makinggung; Jemmry Recy Winokan; Margaretha Rundengan (Universitas Merdeka Madiun, 2022)
— The Malalayang Dua sub-district still has a large area of ??land planted with coconuts. Along with the price of cooking oil that continues to increase, it is deemed necessary to invite partners to take advantage of the available resources. Thus, training in making coconut oil is an option in this community service activity. The training on making coconut oil was delivered directly by instructors from the Balai Penelitian Tanaman Palma. This activity is quite aimed at utilizing coconut plants that are widely available in partner areas so that they can be used properly so that they can be used for household needs and can even be sold to increase family income. In addition, provide material on how to start a business. Starting from how to find business ideas in brain storming methode and how to run a business. The method of implementation is to make observations in advance about the needs of partners, conduct training on how to make coconut oil, present materials and discussions.